Analysis of Company Productivity Using The American Productivity Center Model (APC Models) Approach - Nuryadin (Journal Basic Science and Technology, 2022)
Today, industrial competition is increasingly competitive and complex, along with advances in science and technology that are increasingly integrated. So like it or not, every company competes to continue to improve the company's performance so that it continues to exist in the competitive arena. The classic problem experienced by each company is the limited human resources and technology they have, so optimizing the conversion of resources such as: Labor, Raw Materials Energy Capital and technology should be the main focus in company policies so as to create a life cycle and company performance that is healthy so that it can provide maximum benefits and have high competitiveness. Productivity analysis using the American Productivity Center Model (APC Model) approach is a productivity analysis based on index numbers that can provide an overview of the company's productivity and profitability growth and can provide information to company management about which resources or inputs are not optimal in conversion. which causes a decrease in company performance so that improvement steps can be taken early and continuously. Research results at PT. Mirasa Indo Food Industry which is located at JI. Munggur No. 2 Ambar Ketawang, Mungkid, Magelang. During the period 2002 to 2003, it turned out that in 2003 productivity decreased by 3.34% while profitability increased by 23. 22% in 2003 there was also an increase in the total input of 1.266%. From the results of the research that has been done, it can be seen that the productivity level has decreased and the profitability has increased.